Synthesis and Evaluation of the Antioxidant Activity of Lipophilic Phenethyl Trifluoroacetate Esters by In Vitro ABTS, DPPH and in Cell-Culture DCF Assays - Bernini, Roberta (Molecules, 2018)
Polyphenols are natural compounds showing a variety of health-promoting effects. Unfortunately, due to low lipid solubility, their applications in the pharmaceutical, food, and cosmetic industries are limited. With the aim of obtaining novel lipophilic derivatives, the present study reports the synthesis of a series of phenethyl trifluoroacetate esters containing up to two hydroxyl groups in the aromatic ring. Experimental logP values confirmed a greater lipophilicity of the novel compounds compared to the parent compounds. The radical scavenging capacity of all phenethyl trifluoroacetate esters was evaluated by in vitro assays (ABTS, DPPH) and in cultured cells (L6 myoblasts and THP-1 leukemic monocytes) using 2′,7′-dichlorodihydrofluorescein diacetate. These data revealed that the esters showed a good antioxidant effect that was strictly dependent on the grade of hydroxylation of the phenyl ring. The lack of toxicity, evaluated by the MTT assay and proliferation curves, makes these trifluoroacetates attractive derivatives for pharmaceutical, food, and cosmetic applications.